ANALISIS FRAMING EPISODE “MEREKA RAMAI-RAMAI MENGGUGAT KPK” PADA PROGRAM REALITAS METRO TV - Z I, Shabrina; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Early 2015 in Indonesia is dominated by the feud between the Corruption Eradication Commission (KPK) and the Indonesian National Police (INP). Realitas is an investigative news program in Metro TV that review more into the news. Realitas review the feud between the KPK and the National Police in the episode "They are busy to sue KPK" that aired on January 27, 2014. Authors interested to know more framing done by Reality related dispute between the Commission and the National Police. The aim of this study was to determine the framing analysis episode "They are busy to sue KPK" on Metro TV program Realitas.This study uses a qualitative method analysis model framing Robert Entman. Data collection techniques used is through observation and documentation. As for the examination of the validity of data researchers used a technique of persistence observation.Results of the study found that Realitas framed the the KPK case as a group or individual efforts to weaken the KPK. The weakening over attacks and reporting to the KPK dignitaries. Weakening efforts has any connection with the determination of Commissioner General Budi Gunawan as a suspect by the KPK. President Joko Widodo urged to mediate in case of dispute the KPK and the National Police. The issue of criminalization of the KPK that appear in this episode so that the people think it is an attempt to criminalize the the KPK dignitaries.Keyword : Analysis Framing, KPK, Polri